Effects of celecoxib on AQP-1, NF-κB and apoptosis in lung tissue of neonatal rats with hyperoxia-induced lung injury: Effects of celecoxib on neonatal rats - Fan, Zhengfei; Shen, Yuan (Cellular and Molecular Biology, 2023)
To analyze the effects of AQP-1, NF-κB and apoptosis in lung tissue of neonatal rats with hyperoxia-induced lung injury (HILI).162 neonatal SD rats were divided into control group (COG), model group (MOG) and celecoxib group (CEG), 54 rats in each group. Each group was subdivided into 1st, 5th and 10th-day groups with 18 rats in each group. The neonatal rat model of HILI was established. Nine rats in each group were randomly selected on the 3rd, 6th and 12th day respectively. The level of oxidative stress (OS) in bronchoalveolar lavage fluid (BALF), the pathological changes of lung tissue, the ratio of lung wet weight to dry weight (W/D), the expression of inflammatory factors in lung tissue, the l AQP-1 and NF-κB level and apoptosis in lung tissue were tested. In comparison with COG, the level of MDA in BALF, the ratio of lung W/D, the expression level of IL-6, TNF- α, NF- κB and the number of apoptotic cells in lung tissue were significantly increased, while the level of SOD in BALF and AQP-1 in lung tissue notably decreased in the MOG (P<0.05). The level of malondialdehyde (MDA) in BALF, the ratio of lung W/D, IL-6, TNF-α, NF-κB and plenty of apoptotic cells in lung tissue in CEG were notably decreased than MOG(P<0.05), while the level of SOD in BALF and AQP-1 in lung tissue were raised in CEG. In the COG, the lung tissue structure was complete, the arrangement was neat, the alveolar cavity was clear, and there was no inflammatory infiltration. With the extension of time, the inflammatory infiltration of lung tissue in the MOG gradually increased, the plenty of red blood cells gradually increased, and the size of the alveolar cavity varied; compared with the MOG, the inflammatory infiltration in the CEG decreased and the plenty of red blood cells decreased. Celecoxib can improve oxidative injury, inhibit inflammation, up-regulate AQP-1 and down-regulate NF-κB, inhibit apoptosis, and have a certain protective effect on HILI in neonatal rats.